(untitled) (Vietnam Journal of Community Medicine, 2023)
Background, objectives: A cross-sectional study was conducted on 406 inpatients at the Gastrointestinal Surgery Department of Viet Duc Hospital in 2023 to investigate how satisfied patients undergoing gastrointestinal surgery were and what factors influenced their satisfaction. Results: The overall patient satisfaction rates were as follows: general satisfaction, satisfaction with admission and discharge procedures, satisfaction with physician’s medical treatment, satisfaction with nursing care and communication, satisfaction with medication instructions, satisfaction with facilities and equipment, and satisfaction with service activities were 65.5%, 91.9%, 96.8%, 60.6%, 97.3%, 95.1%, and 93.8%, respectively. Factors such as surgical complications, preoperative and operative counseling, complications due to intervention, and cancer diagnosis were found to be related to patient satisfaction. Conclusion: The overall patient satisfaction rate with the quality of service at the Gastrointestinal Surgery Department was 65.5%; 91.9% of patients were satisfied with admission and discharge procedures; 96.8% were satisfied with physician’s medical care; 60.6% were satisfied with nursing care and communication with healthcare staff; 97.3% were satisfied with medication instructions; 95.1% were satisfied with facilities and equipment, and 93.8% were satisfied with maternity services. Factors related to patient satisfaction consisted surgical complications, preoperative and operative counseling, and cancer diagnosis.